SPECTROPHOTOMETRIC DETERMINATION OF DORIPENEM, ERTAPENEM IN BULK AND INJECTION FORMULATIONS BY F-C REAGENT (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Two simple and cost effective spectrophotometric methods were described for the determination of Doripenem and Ertapenem in pure form and in pharmaceutical formulations. The method is based on the formation of blue colored chromogen when the drug reacts with Folin-Ciocalteu (F-C) reagent in alkaline medium. The colored species has an absorption maximum at 725 nm for Doripenem (Method A); 848 nm for Ertapenem (Method B) and obeys beer’s law in the concentration range 0.02-0.1 mg/mL for both Doripenem and Ertapenem. The apparent molar absorptivities were 1.26×10-5, 7.86×10-6 and sandell’s sensitivity was 6×10-4 respectively for Doripenem and Ertapenem. The slopes were 0.3371 ± 0.01245, 0.2611 ± 0.004327 and intercept of the equation of the regression line are 0.02857 ± 0.01885, -0.008095 ± 0.006550 for Doripenem and Ertapenem respectively. The optimum experimental parameters for the reaction have been studied and the validity of the described procedure was assessed. Statistical analysis of the results has been carried out revealing high accuracy and good precision. The proposed method was successfully applied for the determination of Doripenem and Ertapenem in pharmaceutical formulations.